Evaluasi Perbandingan Volume dan Biaya Menggunakan Software Autodesk Revit pada Pekerjaan Struktur Baja Proyek Pembangunan Gedung Kantor PT Tri Kanigara Group - Wibowo, Ari; Beatrix, Michella (Politeknik Negeri Lhokseumawe, 2024)
With the advancement of technology, the utilization of Building Information Modeling (BIM) software such as Autodesk Revit is becoming increasingly common in the construction industry. The Quantity Take Off (QTO) process in Autodesk Revit involves calculating and identifying the quantity of construction materials required for a 3D model-based project created using Autodesk Revit software. The objective of this research is to evaluate the use of steel structure materials and cost estimates generated through Autodesk Revit. In the QTO calculations using Autodesk Revit, there is a difference in both volume and total cost compared to conventional calculations. Conventional calculations result in a total cost of Rp. 798,352,660.00, while the output from Autodesk Revit is Rp. 786,321,269.47. The difference between these two amounts is Rp. 12,031,390.53, meaning that the percentage is 0.76% more economical using Autodesk Revit. The volume details are as follows: WF size 500x200x10x6 mm has a percentage difference of 3.89% larger when using Autodesk Revit, WF size 400x200x7x11 mm has a percentage difference of 8.15% larger when using Autodesk Revit, WF size 350x175x7x11 mm has a percentage difference of 34.27% larger using conventional calculations, WF size 250x125x6x9 mm has a percentage difference of 1.78% larger when using Autodesk Revit, WF size 150x75x5x7 mm has a percentage difference of 0.46% larger when using Autodesk Revit, and bolt threads have a percentage difference of 7.35% larger using conventional calculations.